Neuropathology of mitochondrial diseases. Issue 1 (13th June 2007) - Filosto, Massimiliano; Tomelleri, Giuliano; Tonin, Paola; Scarpelli, Mauro; Vattemi, Gaetano; Rizzuto, Nicolò; Padovani, Alessandro; Simonati, Alessandro
Abstract : The term "mitochondrial diseases" (MD) refers to a group of disorders related to respiratory chain dysfunction. Clinical features are usually extremely heterogeneous because MD may involve several tissues with different degrees of severity. Muscle and brain are mostly affected, probably because of their high dependence on oxidative metabolism. Muscle can be the only affected tissue or involved as a part of a multi-system disease; ragged red fibers, accumulation of structurally altered mitochondria and cytochrome-c-oxidase (COX) negative fibers are the main pathological features. In mitochondrial encephalopathies, central nervous system (CNS) structures are affected according to different patterns of distribution and severity. Characteristic lesions are neuronal loss, vasculo-necrotic changes, gliosis, demyelination and spongy degeneration. In accordance with either grey matter or white matter involvement two main groups of diseases may be distinguished. Neuronal loss and vasculo-necrotic multifocal lesions are the common features of grey matter involvement; demyelination and spongy degeneration occur when white matter is affected, often associated with less severe lesions of the grey structures. Grey matter lesions are prevalent in MERRF, MELAS, Alpers and Leigh syndromes. White matter involvement is always seen in Kearns-Sayre syndrome and was recently described in mtDNA depletion syndrome linked to dGK mutations and in the rare conditions associated with complex I and II deficiency. In this review we describe the main histopathological features of muscle and CNS lesions in mitochondrial diseases.